A Rapp-Hodgkin like syndrome in three sibs: clinical, dental and dermatoglyphic study - (:unkn) unknown (My University, 1999)
Rapp-Hodgkin ectodermal dysplasia is an autosomal dominant disorder characterized by distinctive craniofacies, cleft lip or palate, oligodontia or anodontia, hypoplasia of the nails, and a decrease in or absence of the sweat glands and hair follicles. We have identified a family in which three children display clinical features similar to Rapp-Hodgkin syndrome. The father and two other sisters of the patient had normal facial features, but had short stature and had dental anomalies, the latter suggestive of ectodermal dysplasia. The overall clinical, dental, and dermatoglyphic findings of these patients are discussed in relation to reports of families with Rapp-Hodgkin syndrome.
Keywords: Adult; Female; Humans; Middle Aged; Syndrome; Adolescent; Male; Child; Abnormalities, Multiple; Ectodermal Dysplasia; Pedigree; Dermatoglyphics; Tooth Abnormalities